Estudio de factibilidad para la creación de una empresa comercializadora de repuestos y accesorios para vehículos automotores (2015)
The Project entitled (study of factibility to créate company of accessories and auto parts in Armenia city) was made by Carolina González Muñoz and José Alejandro Bermudez Ocampo for opting for the profesional degree of business administrator. This Project has been developed in order to fin dan opportunity for the City of Armenia in the autopart and automotive sectors in general, in the same way, applying the knowledge acquired in the professional training process. Looking for the feasibility of creating a Supply of Spares And Accessories For Motor Vehicles Company in the city, which is certainly one of the factors with most demand in the market, because it is evident the number of vehicles which are purchased every day. For the realization of this work, it was necessary to make an approach with the auto part’s business owner in the city of Armenia, as well as those working in the field of automotive maintenance, besides this has been based on the stores that are located in the City of Pitalito (Huila), which have been managed by close relatives of those who have been developing the Project in this way, it has been possible to get information about market, technical, administrative, environmental and financial aspects, to get their completion, so their viability and thriving realization are proved.